Improved HILIC LC/MS of Heparinoids using a Chip with Post-column Make-up Flow - Staples, Gregory O. (2010)
Heparan Sulfate (HS) and heparin are linear, heterogeneous carbohydrates of the glycosaminoglycan (GAG) family that are modified by N-acetylation, N-sulfation, O-sulfation, and uronic acid epimerization. HS interacts with growth factors in the extracellular matrix, thereby modulating signaling pathways that govern cell growth, development, differentiation, proliferation, and adhesion. HPLC-chip-based hydrophilic interaction liquid chromatography/mass spectrometry has emerged as a method for analyzing the domain structure of GAGs. However, analysis of highly sulfated GAG structures decasaccharide or larger in size has been limited by spray instability in the negative-ion mode. This report demonstrates that addition of post-column make-up flow to the amide-HPLC-chip configuration permits robust and reproducible analysis of extended GAG domains (up to degree of polymerization 18) from HS and heparin. This platform provides quantitative information regarding oligosaccharide profile, degree of sulfation, and non-reducing chain termini. It is expected that this technology will enable quantitative, comparative glycomics profiling of extended GAG oligosaccharide domains of functional interest.